Effectiveness of a role-modeling intervention on student nurse simulation competency - Aronson, Barbara; Glynn, Barbara; Squires, Timothy (Clinical Simulation in Nursing, 2013)
Novice nurses are often inadequately prepared to respond to complex, patient care situations where patients' conditions deteriorate. Exposure to a video-taped intervention that role-models and reinforces expected behavior of an expert nurse before participation in a simulation may improve student nurse performance in a cost-effective manner. The primary purpose of this quasi-experimental pre-test, post-test study was to assess the preliminary effectiveness of a theory based role-modeling intervention on enhancing student nurse competency in responding to a simulated response to rescue event. Performance was measured by a previously validated Heart Failure Simulation Competency Evaluation Tool (c) (HFSCET). Total mean scores on the HFSCET for the pre-test (59.08) and post-test (87.08) were significantly different (p = .000); students performed better on the post-test after exposure to the role-modeling intervention. A power analysis indicated a large effect size (effect size = .926; alpha = 0.50; power = 0.991). Students who had a greater number of days between the intervention and the post-test had a lower score. This innovative intervention based on established learning theory may change the way educators prepare novice students to achieve expected clinical competencies in graded simulation performance assessments. (c) 2013 International Nursing Association for Clinical Simulation and Learning. Published by Elsevier Inc. All rights reserved.
Keywords: Intervention; Nursing students; Performance assessment; Simulation; dept.nur

Competency assessment in simulated response to rescue events - Aronson, Barbara; Glynn, Barbara; Squires, Timothy (Clinical Simulation in Nursing, 2012)
Background: Reliable and valid instruments are needed to assess patient safety competencies, specifically nursing students' ability to appropriately respond to simulated rescue events. Methods: This was an instrument development study conducted with 152 senior nursing students in 2 phases. Results: Student groups performed poorly during the simulation scenario, with mean scores on the Heart Failure Simulation Competency Evaluation Tool ranging from 46% to 56%. Interrater reliability increased to .839 after item revision during Phase 2 of the study. Discussion: This simulation competency assessment package is ready to be tested with more diverse student groups and novice nurses in the practice setting. © 2012 International Nursing Association for Clinical Simulation and Learning.
Keywords: Failure to rescue; Instrument development; Nursing students; Patient safety; Simulation; dept.nur